A case review of a patient experience of photopheresis using a peripherally inserted central catheter. Issue 1 (10th November 2018) - Rushton, Cherie; Jackson, Andrew; Goddard, Kathryn; Alfred, Arun
Abstract: Extracorporeal photopheresis (ECP) is a cell based immunomodulatory therapy in which the patient is attached intravenously to a cell separating machine. During ECP a patient's blood is collected via either a central venous access device (CVAD) or a peripherally inserted 16G arterial venous fistula needle in either one or both antecubital fossa. However, patients presenting for ECP with GVHD repeatedly present a challenge to the ECP team due to poor venous access resulting from previous therapies and skin changes. The use of peripherally inserted central venous catheters (PICCs) offers an alternative route of vascular access for this cohort of patients. Here we present a case report of a patient successfully treated with ECP following the insertion of a PICC line.